Advances in epidemiological research on effects of air pollution on skin diseases - Chengyao SUN; Dajing TANG; Fengge CHEN; Chuan ZHAO; Mingyang GUAN (环境与职业医学, 2022)
Air pollution is a major environmental threat to human health, and skin, as the largest organ of the human body, is a major exposure route of air pollutants, so the correlations between air pollutants and skin diseases are noteworthy to study. This paper reviewed the acute effects of air pollutants on the risks of dermatosis outpatient and emergency visits at home and abroad, especially on dermatitis, eczema, urticaria, acne, psoriasis, and other skin diseases with high prevalence rates and heavy disease burdens. The effects of air pollutants on skin diseases are affected by exposure characteristics of air pollutants (such as composition, concentration, and exposure time), environmental factors (such as temperature, humidity, and ultraviolet), and population characteristics. In view of insufficient evidence on the long-term effects of air pollutants on skin diseases and the interaction of environmental factors, future research directions were prospected, aiming to provide new ideas for further study on the effects of air pollutants on skin diseases and the formulation of relevant prevention and control strategies.